CRITICAL CONSIDERATIONS ABOUT THE BIBLIOGRAPHICAL REFERENCE SYSTEM KNOWN BY HIS ENGLISH ACRONYMS AS APA - Alemán, Aníbal; Quezada, Freddy (Universidad Nacional Autónoma de Nicaragua, Managua. UNAN-Managua, 2014)
This essay aims to start a debate upon a subject that has been shortly discussed within university community, but of great presence into academic environment: role reference and citation system known as APA style plays in different time to student education, and in process of teacher´s research. Ideas set in this paper, aims to highlight nature and roll of a reference system that coming fromnorth academy, which has been assumed without much criticism by Latin American institutions. However critical analysis is done upon what stands behind of APA rules, as the necessity to control individual author representation, questioned by flow of information, messages and texts, through different media or source, of unsuspected limits until few decades ago.Keywords: APA style, references and citation system, mass media